Fourth Plan Report of the Working Group on Structurals (Group IX - November, 1964) - Planning Commission (Planning Commission, 1964)
A break up list of machinery required for Structural/ Crane manufacturing projects, as listed in appendices I to VI, was given to the convenor of Working Group VI—Machine Tools for necessary action. These lists of machinery and plant are comprehensive, and economy could be effected by utilizing modern all welded fabrication methods, and by having forging and gear cutting work sub-contracted to firms with specialized plant to undertake this work. Gear cutting capacity at present available is largely captive making it difficult to obtain regular supplies. It if expected that nearly 40% of The machinery mentioned al I and II above will be available indigeneously. The replacement of machinery in existing works and site erection plant would amount to approximately - crores per annum in terms of foreign exchange. The Advisory Panel recommended at para 18 below will base to operate this foreign exchange ceiling.
Report of the Working Group on Structurals (Group IX - November, 1964)
Planning Group on Machinery Industries